Grow Minnesota!®: Using grassroots data to support business growth and retention in the state of Minnesota. Issue 2 (15th March 2017) - O'Neil, Sean; Schaff, Kathi; Riffe, Angela
Abstract: The Minnesota Chamber of Commerce's Grow Minnesota! program serves as a premier, private sector-led business retention and expansion program. The program operates statewide through partnerships with close to 80 local chambers of commerce and economic development organizations. Grow Minnesota! turns visit data into action in four distinct ways: (1) one-on-one business assistance, (2) events, forums, or one-time initiatives to address specific business concerns, (3) large-scale programs and projects, and (4) public policy initiatives to improve the business climate in Minnesota. The Grow Minnesota! program has resulted in strong partnerships with public and private entities throughout the state, helping to foster a robust ecosystem of resources that collectively serve businesses and drive economic development in Minnesota.